Business Opportunity : Golden Network / Nuraida Syamimi Mohd Azuki - Mohd Azuki, Nuraida Syamimi (2021)
To do a business opportunity for the sake of Fundamental of Entrepreneurship (ENT300) course requirement, me and classmates must do an individual task. This business opportunity required us to use a company that we choose to do the case study before. From the company which is Golden Network, I have to make an innovation for any product that I want. So that, I chooses a few products to make an innovation. From the innovation, I need to build a business model canvas for my innovation product. The business model canvas is a one page overview that lays out both what I want to do and how I go about doing it. It is enabling structured conversations around management and strategy by laying out the crucial activities and challenges involved with your initiative and how they relate to each other. The business model canvas includes nine components such as key partners, key activities, key resources, value proposition, customer relationships, distribution channel, customer segment, cost structure and revenue stream.